Solanum Fruits: Phytochemicals, Bioaccessibility and Bioavailability, and Their Relationship With Their Health-Promoting Effects - Elizalde-Romero, Cristina Alicia; Montoya-Inzunza, Luis Aurelio; Contreras-Angulo, Laura Aracely; Heredia, J. Basilio; Gutiérrez-Grijalva, Erick Paul (Frontiers in Nutrition, 2021)
The Solanum genus is the largest in the Solanaceae family containing around 2,000 species. There is a great number of edibles obtained from this genus, and globally, the most common are tomato (S. lycopersicum), potato (S. tuberosum), and eggplant (S. melongena). Other fruits are common in specific regions and countries, for instance, S. nigrum, S. torvum, S. betaceum, and S. stramonifolium. Various reports have shown that flavonoids, phenolic acids, alkaloids, saponins, and other molecules can be found in these plants. These molecules are associated with various health-promoting properties against many noncommunicable diseases, the main causes of death globally. Nonetheless, the transformations of the structure of antioxidants caused by cooking methods and gastrointestinal digestion impact their potential benefits and must be considered. This review provides information about antioxidant compounds, their bioaccessibility and bioavailability, and their health-promoting effects. Careful consideration of this information may be pivotal to modulate the health benefits of fruits of the Solanum genus for numerous diseases prevention and treatment.